Responding to the challenge of AI: Retrieving human intelligence through labour. - Agustí-Panareda, Jordi; Agustí-Cullell, Jaume (International Labour Review, 2025)
The article focuses on the relationship between artificial intelligence (AI) and human intelligence (HI) in the context of labour, arguing that current fascination and fear of AI stem from a limited understanding of HI that neglects its full potential. It presents a framework defining HI through five constitutive creative powers—interest in reality, communication, subsidiary symbiosis, generalized research, and freedom—and three intertwined dimensions: functional, axiological (value-creating), and liberating intelligence. The authors contend that labour is a crucial arena for cultivating these broader aspects of HI, which AI cannot replicate, and emphasize the need to humanize work by fostering collective creativity, ethical judgment, and adaptability. They recommend aligning work with genuine interest, promoting meaningful communication, organizing labour through cooperative networks, encouraging inquiry and creativity, and redefining incentive systems to support HI development. Additionally, the article proposes treating AI as a complementary tool to HI, introducing new professional roles called AI–HI mediators to oversee this synergy, and highlights the role of international organizations, particularly the International Labour Organization (ILO), in guiding human-centred AI governance in the workplace.